Literature review study: the effect of metaverse as a learning environment for civic competence - Purwani, Ririn; Ripanti, Eva Paja; Sirait, Judyanto; Yani, Ahmad; Warneri (Universitas Tanjungpura, 2026)
This study examines the potential of the metaverse as a learning environment to support the development of civic competence in the digital era. A Systematic Literature Review (SLR) was conducted by analyzing 30 peer‑reviewed articles published between 2020 and 2025 discussing the use of metaverse, virtual reality (VR), and augmented reality (AR) in educational contexts. The review followed structured procedures including database searching, article screening, data extraction, and narrative synthesis following PRISMA guidelines. The findings indicate that metaverse‑based learning environments have strong potential to enhance civic competence through increased engagement, collaboration, experiential learning, and digital participation. Immersive environments allow learners to explore social issues, interact with peers through avatars, and practice democratic participation within simulated contexts. However, challenges remain, including infrastructure costs, digital literacy gaps among educators, and unequal technological access. Collaboration among policymakers, educational institutions, and technology developers is necessary to ensure equitable and sustainable implementation. Future research should conduct empirical and longitudinal studies to examine the long‑term impact of metaverse‑based learning environments on civic competence development.